Representações sociais sobre docência na educação infantil na interface com a política de formação de professores - Nóbrega, Suely Soares (2012)
This research aims at analyzing Social Representations about the teaching of future educators of the Federal University of Rio Grande do Norte (Caicó) in early childhood education. We assumed that teaching in early childhood education, in a problematical conception, is the commitment to freedom of educators and students, subjects of educational practice, based on knowing act that stimulates critical thinking, creativity, reflection and action upon reality. Thus, we reflect on the policies formulated concerning early childhood education and teacher training in the current context. Using the Theory of Social Representations formulated by Moscovici, we investigate the importance of training processes in the Social Representations of future educators, analyzing the CNE/CP 1, May 15, 2006. 118 undergraduate students who were in the first, third, fifth, seventh and ninth semesters of the Pedagogy Course participated in this research. First, we used a questionnaire of Free Association of Words in which was evoked, in order of importance, the stimulus in teaching in early childhood education, and secondly, through a semi structured interview, we analyzed the expectations of the students for the Pedagogy Course and which elements they considered relevant to the training of teachers of early childhood education. To process the data the software EVOC and ALCESTE was used. The results of this research lead us to reflect on the knowledge that constitutes the teaching practice no matter they are based on experience, science, ethics, political or sociocultural terms. The Social Representations of future teachers about teaching in early childhood education refers to the commitment to the education of young children and also to the teacher education itself, besides showing the romantic vision of teaching. The implications for the initial teacher training that appear in the Social Representations of the Pedagogy students of UFRN/CERES consist of the ability to develop and implement public policies that make commitments with the formation of the citizen child, recognizing their specificities; valuing recreation as science, comprising interfaces for children's development and establishing teaching as a profession. Prospective teachers assume the responsibility and commitment to the education of children, emphasizing the aspects of morality and education, besides patience and dedication. They also recognize the need to link playing, caring and education, even though among trainees, recognition of theory in educational practice has not been evidenced. We propose to the teacher training policies a partnership between universities and early childhood education institutions that may provide opportunities for future teachers to participate in the political-pedagogical project of the Pedagogy Course. Finally, we hope this study will contribute to the construction of knowledge and reflection of teacher education, especially concerning early childhood education, which considers children‟s education an essential point for their total development. This work contributed to new researches concerning teaching in early childhood education and its role in the teaching-learning process, providing total children development in the full sense of childhood.